2023
DOI: 10.1038/s41598-023-30250-6
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis BCG increase the selected determinants of monocyte/macrophage activity, which were diminished in response to gastric pathogen Helicobacter pylori

Abstract: High antibiotic resistance of gastric pathogen Helicobacter pylori (Hp) and the ability to escape the host immune response prompt searching for therapeutic immunomodulators. Bacillus Calmette–Guerin (BCG) vaccine with Mycobacterium bovis (Mb) is a candidate for modulation the activity of immunocompetent cells, and onco-BCG formulation was successfully used in immunotherapy of bladder cancer. We determined the influence of onco-BCG on the phagocytic capacity of human THP-1 monocyte/macrophage cells, using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…In this study, BMDM, as previously human THP-1 derived macrophages 29 , were treated for 24 h (induction-priming), with M. bovis BCG, and then the engulfment capacity of macrophages was evaluated. Furthermore, the influence of macrophage priming with mycobacteria on CD11b integrin expression and the level of total DNA methylation was determined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, BMDM, as previously human THP-1 derived macrophages 29 , were treated for 24 h (induction-priming), with M. bovis BCG, and then the engulfment capacity of macrophages was evaluated. Furthermore, the influence of macrophage priming with mycobacteria on CD11b integrin expression and the level of total DNA methylation was determined.…”
Section: Resultsmentioning
confidence: 99%
“…CHI, CHI-Plur and CHI-GlcNAc solutions were prepared as described above. Then, 1 mL of M. bovis onco-BCG 3 × 10 8 CFU/mL was added to each type of solution, previously labelled with BacLight fluorescent dye tracer for 30 min at room temperature, which penetrates only into living cells, as previously described 29 . The labelled bacteria were then added to the prepared CHI solutions, and spray-dried as described above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, BCG was found to augment the phagocytic capacity of human THP-1 monocytes/macrophages against H. pylori, by increasing the expression of the surface integrins CD11b, CD11d and CD18, as well as the membrane and soluble lipopolysaccharide receptors CD14 and sCD14, ultimately reducing the incidence of GC. 263 Another study reported that intratumoral delivery of the prophylactic yellow fever vaccine (live 17D) into mice stimulated immune-mediated antitumor effects including the orchestration of cytotoxic T lymphocytes and suppression of Tregs. 264 Intriguingly, Tai et al found that administering a single dose of the influenza vaccine intramuscularly a day before surgery optimally activated NK cells in specific murine models.…”
Section: Immune Microenvironmentmentioning
confidence: 99%